Censorship, Control and Resistance in Eugene O’Neill’s “black plays” The Emperor Jones and All God’s Chillun Got Wings - Gwenola Le Bastard (Revue LISA)
The 1920s were a period of control, restriction and censorship on the American stage. From its creation in 1922 to its dismantling in 1927, the Play Jury was in charge of theater regulation in the United States, at a time when segregation was still enforced on the stage. White actors with their faces painted black played the roles of the black characters, while black audiences were generally denied access to Broadway theaters. In this context of severe prohibition and regulation, Eugene O’Neill wrote and produced The Emperor Jones (1920) and All God’s Chillun Got Wings (1923), two plays which bear witness to the then rising interest of white avant-garde writers and artists in African-American life and culture, and to their productive connection with the emerging literature of the Harlem Renaissance. But these two controversial plays (each of which featured a black actor in the leading role) also highlighted the difficulty of tampering with the “color line”. These two “black plays” raise the issues of censorship and resistance both at the level of their writing and in connection with their production and reception. This paper aims at arguing that they can be read as attempts to push back the limits of artistic expression on textual, scenic and social grounds simultaneously. In particular, O’Neill’s expressionistic techniques in the plays, with their symbolist staging and inexorably shrinking and oppressive settings, may be seen as a dramatization of the limitations of the American stage, which was then unable to accommodate his vision of a reshaped and modernized theater as well as the idea of a more tolerant American society. It is consequently possible to consider these two plays, which feature prominently the struggle against censorship both at the textual and institutional levels, as the beginning of major changes which occurred from the 1920s onwards.